2020
DOI: 10.14710/jil.18.1.48-57
|View full text |Cite
|
Sign up to set email alerts
|

Idealisme dan Dualisme Daur Ulang Sampah di Indonesia: Studi Kasus Kota Semarang

Abstract: This study analyzes various regulations on urban waste management, with emphasis in recycling activities. How regulatory frameworks from the national level translates to the city level, and the extent of its implementation are examined through field observations in the city of Semarang as a case study. Based on the study of regulations and policy documents, this study suggests that recycling is found in various policy domains, not only those concerning waste management but also in the environment, industry, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Dilation is the process of expanding or thickening the shapes or objects in an image. The dilation formula is calculated using Equation (2).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dilation is the process of expanding or thickening the shapes or objects in an image. The dilation formula is calculated using Equation (2).…”
Section: Data Collectionmentioning
confidence: 99%
“…To this day, waste management is a persistent concern [1]. Numerous studies have identified waste as a serious barrier all across the world [1][2][3][4]. For example, during Eid al-Fitr, Yogyakarta, Indonesia, encountered waste accumulation issues due to all employees celebrating the holiday.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diperkirakan bahwa jumlah sampah secara global akan meningkat tiga kali lipat di tahun 2100 dan sekitar 11 juta ton sampah perkotaan akan dihasilkan per hari (Seacat and Boileau, 2018) dalam (Setiadi et al, 2020).Upaya pengelolaan sampah tidak saja menjadi tanggung jawab pemerintah saja, namun perlu dilakukan secara bersama-sama. Tidak dapat dipungkiri makhluk hidup sangat bergantung dengan alam, kita wajib menjaga, melestarikan dan membuat bumi menjadi tempat yang layak untuk ditinggali, tidak hanya untuk kebutuhan kita saat ini, tetapi juga untuk generasi yang akan datang.…”
Section: Pendahuluanunclassified
“…This waste problem also occurs in areas in Indonesia including Malang Regency. The issue of waste in Indonesia and other countries is a business that is decentralized to local governments (Setiadi et al, 2020). Data on waste management facilities from the National Waste Management Information Source (SIPSN) at the Malang Regency Landfill (Ministry of Environment and Forestry): The amount of waste in the Talangagung education tourism landfill is the most compared to other landfills in Malang Regency.…”
Section: Introductionmentioning
confidence: 99%